E-Learning Initiatives at CTEVT: An Attempt at Innovation and Paradigm Shift in TVET Pedagogy - Pangeni, Shesha Kanta; Karki, Gehendra (Journal of Technical and Vocational Education and Training, 2021)
Information and communication technology (ICT) has brought innovative approaches to teaching and learning introducing pedagogical innovation that leads to paradigm shift in education. However, Technical and Vocational Education and Training (TVET) sector in Nepal has little exposure to ICT integrated pedagogical practices. In this context, this paper presents lessons from e-learning initiatives at CTEVT based on a study on e-learning pilot projects from three leading technical schools. It uses both qualitative and quantitative data received from 152 survey responses, two focused group discussions and 10 individual interviews. The study reports that e-learning is promising for TVET sector as an innovative ICT integrated alternative pedagogy. However, instructors and schools want additional support for training and ICT infrastructures to design, develop and implement courses for e-learning locally. The study also draws implications to scale up the initiations and interventions of e-learning at institutional level that are meaningful for expansion of similar pilot projects, ICT integration across TVET programs offered by CTEVT, pedagogical innovation, workplace learning opportunity for students, increase access and quality in TVET programs and institutional reform.